2000
DOI: 10.1046/j.1365-313x.2000.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of intrachromosomal homologous recombination in Arabidopsis overexpressing the MIM gene

Abstract: SummaryThe Arabidopsis MIM gene encodes a protein belonging to the SMC family (structure maintenance of chromosomes) which is required for intrachromosomal homologous recombination (ICR). Both ICR and MIM gene expression are enhanced by DNA-damaging treatments, suggesting that MIM is a factor limiting DNA repair by homologous recombination (HR) under genotoxic stress. We tested this hypothesis by measuring the levels of recombination in the mim mutant under genotoxic stress, using methyl methanesulfonate. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…defective in a calcium binding EF-hand protein) ; while mutation in BRU1 (a novel protein involved in DNA repair and replication) (Takeda et al, 2004), RAD50 (Gherbi et al, 2001), RAD17, or RAD9 (Heitzeberg et al, 2004) only slightly increases HR, whereas teb (a homolog of human DNA polymerase u) (Inagaki et al, 2006), rad51c, or rad51d (a bacterial RecA recombinase homolog) (Durrant et al, 2007), mim (hypersensitive to MMS, irradiation, and MMC, a structural maintenance of chromosome protein) (Mengiste et al, 1999;Hanin et al, 2000), and ino80 (an ortholog of the SWI/SNF ATPase family) mutations apparently decreased HR. We also observed that mutations in ROR1/RPA2A elevated the HR to a similar level as in abo4 mutants (see Supplemental Figure 2 online).…”
Section: Discussionmentioning
confidence: 99%
“…defective in a calcium binding EF-hand protein) ; while mutation in BRU1 (a novel protein involved in DNA repair and replication) (Takeda et al, 2004), RAD50 (Gherbi et al, 2001), RAD17, or RAD9 (Heitzeberg et al, 2004) only slightly increases HR, whereas teb (a homolog of human DNA polymerase u) (Inagaki et al, 2006), rad51c, or rad51d (a bacterial RecA recombinase homolog) (Durrant et al, 2007), mim (hypersensitive to MMS, irradiation, and MMC, a structural maintenance of chromosome protein) (Mengiste et al, 1999;Hanin et al, 2000), and ino80 (an ortholog of the SWI/SNF ATPase family) mutations apparently decreased HR. We also observed that mutations in ROR1/RPA2A elevated the HR to a similar level as in abo4 mutants (see Supplemental Figure 2 online).…”
Section: Discussionmentioning
confidence: 99%
“…A link between chromatin structure, gene silencing, and genome maintenance had been previously proposed for the MIM gene (Hanin et al 2000) and for BRU1, an Arabidopsis gene linking heterochromatin stability to gene silencing as well as to DNA repair (Takedaet al 2004). Our results on DDM1 provide a new example of this link for a chromatin remodeling SWI2/SNF2 gene and further support the link between genetic and epigenetic stability.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting the nucleosome-DNA interactions or remodeling of chromatin via ATP-dependent proteins might thus stimulate HR and DNA repair. In support of this possibility, it was shown that alteration in the expression of MIM, a gene encoding a chromatin structural component related to the SMC family (structure maintenance of chromosomes), could affect the rate of intrachromosomal recombination in Arabidopsis (Hanin et al 2000). BRU1 is an additional example of an Arabidopsis gene linking heterochromatin stability to gene silencing as well as to DNA repair (Takeda et al 2004).…”
mentioning
confidence: 99%
“…Mutants of nuclear protein BRU1 involved in the maintenance of chromatin structure were highly sensitive to genotoxic stress, and were characterized by the increased intrachromosomal homologous recombination [Takeda et al, 2004]. Similarly, the expression of another gene, MIM1, involved in the maintenance of chromosome structure and required for the efficient homologous recombination, was significantly induced by DNA-damaging treatments [Hanin et al, 2000].…”
Section: Chromatin Remodeling Proteins: Shaping and Maintaining Chrommentioning
confidence: 99%